Is it possible to change the psychopathic traits of substance abusers treated in faith-based therapeutic communities – does the length of treatment matter? - Bugarski Ignjatovic, Vojislava V.; Vajagić, Vanja V.; Nikolašević, Željka D. (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Faith-based therapeutic communities (FBTCs) have been increasingly employed as a modality in the treatment of substance abuse. Their program influences behavioral, psychological, cognitive and social changes among their beneficiaries. The aim of the study was to evaluate whether the duration of treatment in a FBTC may contribute to changes in the traits that make the four Hare’s psychopathy dimensions – Antisocial behavior, Lifestyle, Interpersonal relationships, and Psychopathic affect. Another aim was to assess whether abusers on treatment in a FBTC have more pronounced psychopathic traits compared with subjects with no history of substance abuse. Methods. The study included 59 male subjects, of an average age of 29 years, and of different educational levels, who were divided into three groups: substance abusers who had spent one year in the FBTC; substance abusers who had successfully completed a two-year program in the FBTC; and healthy controls with no history of substance abuse. The Psychopathy Assessment Questionnaire (PAQ) was employed to assess the four Hare’s dimensions of psychopathy. Results. There were statistically significant differences among the groups on the Antisocial Behavior dimension. For this dimension, there were differences among non-abusers and both groups of substance abusers, with non-abusers achieving the lowest average scores. There were no statistically significant differences between two groups of substance abusers in any of the studied dimensions. Conclusion. The longer, two-year treatment in the FBTC did not contribute to changes of the psychopathic traits more than the one-year treatment. In addition, subjects with history of substance abuse undergoing treatment in the FBTC had more pronounced psychopathic traits compared with non-abusers.